Breaking the ties that bind: new advances in centrosome biology - Mardin, Balca; Schiebel, Elmar (The journal of cell biology, 2012)
The centrosome, which consists of two centrioles and the surrounding pericentriolar material, is the primary microtubule-organizing center (MTOC) in animal cells. Like chromosomes, centrosomes duplicate once per cell cycle and defects that lead to abnormalities in the number of centrosomes result in genomic instability, a hallmark of most cancer cells. Increasing evidence suggests that the separation of the two centrioles (disengagement) is required for centrosome duplication. After centriole disengagement, a proteinaceous linker is established that still connects the two centrioles. In G2, this linker is resolved (centrosome separation), thereby allowing the centrosomes to separate and form the poles of the bipolar spindle. Recent work has identified new players that regulate these two processes and revealed unexpected mechanisms controlling the centrosome cycle.